Data-driven model (DDM) for collection development and management - Chisaba Pereira, Cristian Alejandro (Qualitative and Quantitative Methods in Libraries, 2021)
DDM for collection development and management is a proposal for capture, analyze, discover insights from data and make proposals from Collection Development and Management to the library of the Pontificia Universidad Javeriana. Our model finds a value for the operation and innovation of the library from the data present in the information systems, repositories, social networks, ERP, CRM, among others. Exploiting the data and designing value proposals for new services or products from the library. Finally, the DDM identifies the profiles for an analytical team for the collection development and management.